The Influence of pricing policies of public services on the willingness to pay for Reduction of Air Pollution in Zimmerman - Gathogo, Mugo Daniel; Mutsembi, Mr. Manundu; Dr. Wafula, Masai (International Journal of Environmental Sciences, 2016)
Purpose: The purpose of this study was to determine pricing policies of public services such as environmental pollution control and management based on the willingness to pay for them. Methodology: System random sampling was used to select the sample of the study. The sample size was limited to 150 households. Ordinary least squares technique was applied in the data analysis to investigate the influence of the identified explanatory variables on the willingness to pay. Results: The study results showed that the size of household, age, marital status of respondent and incidence of a polluted illness in a respondent's household are related to the willingness to pay for reduction in air pollution although they are insignificant at the 95 percent level of significance. Unique contribution to theory, practice and policy: The study recommended setting up of environmental standards to be maintained by the tannery in order to minimize externalities to the residents who pay tax to the government and hence are entitled to clean environments and clean air.